Analysis of long-term dynamics of air temperature fluctuations in the Nura River basin - Zhangozhina, G.M.; Kenzhina, K.D.; Sailauov, D.Ye.; Rakhmetova А.А.; Zhanayeva, M.B. (Fundamental and Experimental Biology, 2024)
In recent decades, a different frequency of dry years has been observed in the Nura River basin in Central Kazakhstan. This article examines the trend of changes in temperature fluctuations over a long period using materials from a separate climate element from the Besoba and Karaganda meteorological stations located in the Nura River basin and the Arkalyk meteorological station located outside the basin, to the west of it, but characterized by similar natural conditions. In the course of research over an 81-year time interval from 1939 to 2019, the absolute and relative frequency of average monthly air temperatures in July in the Nura River basin were established. The meteorological stations under consideration are part of the global international network of meteorological data of Kazhydromet and have constant, accurate series of values of meteorological indicators. Based on the use of the method of statistical analysis, an assessment of the spatio-temporal fluctuations of the temperature regime over a long-term period in the Nura River basin was identified. The study expressed the formation of an arid climate associated with an increase in the average monthly air temperature in the basin of the study area.